A Novel Antibiotic, Rhodomyrtone: Pharmacokinetic Studies in a Murine Model and Optimization and Validation of High-Performance Liquid Chromatographic Method for Plasma Analysis - Tan Suwandecha; Boon-Ek Yingyongnarongkul; Kanokkan Towtawin; Supayang Piyawan Voravuthikunchai; Somchai Sriwiriyajan (MDPI AG, 2024)
Rhodomyrtone has indisputable and undeniable potential as a new antibiotic for antibiotic-resistant Gram-positive bacteria. Therefore, the main objective of this study was to determine the pharmacokinetics profiles of orally administered rhodomyrtone in rats. A reverse-phase HPLC-UV method was developed, optimized and validated for the analysis of rhodomyrtone concentrations in rat plasma. The retention time of papaverine and rhodomyrtone was 3.928 and 5.937 min, with no interference with the excipients used. The lower limit of quantification (LLOQ) of rhodomyrtone in the plasma sample was 0.04 μg/mL, the accuracy of rhodomyrtone at the LLOQ level ranged from 93.64 to 106.36%, precision was 6.59%, 80-120% for accuracy and <20% CV for precision. The calibration curve was linear at concentrations ranging from 0.04 to 128 µg/mL with a correlation coefficient (r) value of equal to or greater than 0.999. Sprague Dawley rats received a single dose of rhodomyrtone at 50 and 100 mg/kg. Blood samples were collected from tail veins. The peak plasma concentration was observed at 2 h, and the area under the curve of rhodomyrtone at 50 mg/kg and 100 mg/kg was 3.41 ± 1.04 and 7.82 ± 1.53 μg·h/mL, respectively. The results demonstrated linear pharmacokinetics characteristics at the studied dosage range. The plasma concentration of rhodomyrtone was above the minimal inhibition concentrations of several common pathogenic bacteria of medical importance. The proposed HPLC-UV method is fast, cost-effective, reliable and reproducible, and it is proposed for the routine analysis of rhodomyrtone.